Case Report: MIS-C Temporarily Associated With COVID-19 Complicated by Reye's Syndrome - Pessoa, Fabrício Silva; Lacerda, Eliza Maria da Costa Brito; Gonçalves, Valdênia Costa; Tanaka, Barbara Neiva (Frontiers in Pediatrics, 2021)
We describe a 7-year-old child with multisystemic inflammatory syndrome that is temporarily associated with the novel coronavirus disease evolving seriously ill, with coronary aneurysm, using human immunoglobulin and acetylsalicylic acid and later complicating the clinical manifestations such as hepatitis, convulsions and coma with Reye's Syndrome. To date, there is no report of the association of multisystemic inflammatory syndrome that is temporarily associated with the novel coronavirus disease and Reye's Syndrome.